Utopie – ostalgie – nostalgie : aller-retour en ex-RDA - Marina Chauliac (Conserveries Mémorielles)
During the twenty years after the fall of the Berlin Wall, from 1989 till 2009, nostalgia took singular social forms in the former GDR. These merit to be analysed throught the history of GDR, the imageries which were transmitted and the current society. The nostalgia of GDR or nostalgie is materialized in a variety of attitudes and feelings about the East German passed society. These can be grouped around two poles: the ostalgie as an enthousiasm for outdated objects and the ostalgie as regret of a model of an egalitarian society. The nostalgia of GDR from a political perspective represents another relationship with the past : it is not any more «nostalgia without memory», nor nostalgia as a reaction of all current inequality, but a «retrogressive Utopia», according to the terms of Jean Séguy, to be understood as a reversed form of a projection in future.